Organocatalyzed coupling of carbon dioxide with epoxides for the synthesis of cyclic carbonates: catalyst design and mechanistic studies. Issue 13 (23rd May 2017) - Alves, M.; Grignard, B.; Mereau, R.; Jerome, C.; Tassaing, T.; Detrembleur, C.
Abstract : The coupling of carbon dioxide (CO2 ) with epoxides with the formation of cyclic carbonates is a highly attractive 100% atom economic reaction. It represents a greener and safer alternative to the conventional synthesis of cyclic carbonates from diols and toxic phosgene. Abstract : The coupling of carbon dioxide (CO2 ) with epoxides with the formation of cyclic carbonates is a highly attractive 100% atom economic reaction. It represents a greener and safer alternative to the conventional synthesis of cyclic carbonates from diols and toxic phosgene. Today, cyclic carbonates find many applications as intermediates for fine chemical synthesis, as electrolytes in Li-ion batteries, and as polar aprotic solvents, and also serve for the synthesis of important polymers such as polycarbonates and polyurethanes. In view of their broad scope and strong economic potential, there is a strong need to improve their synthesis and decrease their production costs. However, CO2 is a thermodynamically stable molecule, and the use of catalysts is therefore mandatory for activating and facilitating the CO2 /epoxide coupling reaction in a selective manner and under mild conditions. Recently organocatalysts have attracted more and more interest in this field and are viewed as alternatives to metal-based ones. Enormous progress has been made these past few years to boost their performances, and some organocatalysts are now very competitive, cheap, and readily available and exhibit good chemical stability towards moisture, water and air. This review focuses on the recent advances in the development of metal-free organocatalysts for the synthesis of cyclic carbonates by CO2 /epoxide coupling. The majority of the state-of-the art organocatalysts used for this reaction are discussed, with special emphasis on the various routes employed to boost their performances. Their mode of action is also reported based on mechanistic considerations, supported by density functional theory (DFT) calculations that are becoming essential tools for modern catalyst design. Such detailed understanding of the mechanisms involving CO2 transformation should pave the way towards the definition of new modes of activation for converting CO2 with a large scope of substrates into various chemicals, monomers and polymers.